“Listen when I come to the table”: Reimagining education with and for Black elementary-aged youth and their mothers - Duane, Addison; Mims, Lauren C. (Frontiers in Education, 2022)
Much of the literature regarding Black youth experiences in schools considers the effects of racism and takes up inquiry through deficit views. Yet, to understand how to shift the system of schooling to provide equitable, liberatory learning experiences, it is critical to center Black children’s voices and perspectives. In the current study, we partnered with eleven Black elementary youth and their mothers to explore their dreams for re-imagining schools. We identified four themes related to school improvement from a child-centered, abolitionist lens. Our findings highlight the need to increase opportunities for youth voice in scholarship and practice, and join existing conversations that see education as the practice of liberation and freedom.